SOCIAL CONFLICT IN PLAYWRIGHT MACBETH BY WILLIAM SHAKESPEARE - Mohammad Zamroni; Veni Kumalasari (JURNAL LITERASI, 2022)
This research analyzes a Social Conflict in Playwright Macbeth by William Shakespeare. The social conflict appears in playwright of Macbeth is about how the taking over of King Scotland’s power by his military leader, Macbeth. In his efforts to seize the power, Macbeth that was aided by his wife and the witches created such social conflict hoping that it would lead him to be the king of Scotland.This research uses theory conflict of Ralf Dahrendorf in which there are two from three means used in this study. Those are latent and manifest interest, and group contradiction and social change.Following the situation created by Macbeth, it was then gave bad impact to the social environment and it lead to social changes.During the time Macbeth as a king and ruled the kingdom, there were many bloodshed which then influenced to people of Scotland’s way of thinking. They thought that the fairness is a foul and the foul is fairness.